The lexicon and meanings of local banana names in Banten: An anthropolinguistics study - Metta Dian Amalia; Asep Muhyidin; Nani Maryani (Universitas Muhammadiyah Malang, 2026)
This research is motivated by the decreasing documentation and understanding of the younger generation regarding the names of local Banten bananas and their philosophical meanings, even though the lexicon represents local wisdom and traditional knowledge of the community. This study aims to examine and describe the lexicon and philosophy of local Banten banana names from an anthropolinguistic perspective as an effort to document culture. The method used is descriptive qualitative with an anthropological approach. Data were obtained through observation, in-depth interviews with 13 informants across four districts in Banten Province, and visual documentation and field notes. From 166 initial data from interviews that have been deduplicated, 62 lexicons of local banana names were obtained, all of which are in the form of attributive endocentric noun phrases. Analysis shows that 57 names still have philosophical meanings that can be explained based on physical characteristics, colour, taste, texture, aroma, consumption habits, and symbolic associations. In contrast, the others have experienced a loss of meaning due to social and generational changes. In conclusion, the lexicon of local Banten banana names serves not only as a varietal marker but also as a cultural archive that reflects the relationship among language, culture, and environment, making its documentation important for preserving the identity and traditional knowledge of the Banten people.